Neuropeptide Y increases differentiation of human olfactory receptor neurons through the Y1 receptor. (December 2019) - Huang, Tsung-Wei; Li, Sheng-Tien; Chen, Duan-Yu; Young, Tai-Horng
Abstract: Olfactory dysfunction significantly impedes the life quality of patients. Neuropeptide Y (NPY) is not only a neurotrophic factor in the rodent olfactory system but also an orexigenic peptide that regulates feeding behavior. NPY increases the olfactory receptor neurons (ORNs) responsivity during starvation; however, whether NPY can promote differentiation of human ORNs remains unexplored. This study investigates the effect of NPY on the differentiation of human olfactory neuroepithelial cells in vitro . Human olfactory neuroepithelium explants were cultured on tissue culture polystyrene dishes for 21 days. Then, cells were cultured with or without NPY at the concentration of 0.5 ng/mℓ for 7 days. The effects of treatment were assessed by phase contrast microscopy, immunocytochemistry and western blot analysis. The further mechanism was evaluated with NPY Y1 receptor-selected antagonist BIBP3226. NPY-treated olfactory neuroepithelial cells exhibited thin bipolar shape, low circularity, low spread area, and long processes. The expression levels of Ascl1, βIII tubulin, GAP43 and OMP were significantly higher in NPY-treated cells than in controls (p < 0.05). NPY-treated olfactory neuroepithelial cells expressed more components of signal transduction apparatuses, Golf and ADCY3, than those without NPY treatment. Western blot analysis also further confirmed these findings (p < 0.05). Additionally, the expression levels of Ascl1, βIII2 tubulin, GAP43, OMP, ADCY3, and Golf in BIBP3226 + NPY and controls were comparable (p > 0.05). NPY not only increases expressions of protein markers of human olfactory neuronal progenitor cells, but also promotes differentiation of ORN and enhances formation of components of olfactory-specific signal transduction pathway through Y1 receptors. Highlights: Neuropeptide Y increases expression of human olfactory neuronal progenitor cells and olfactory receptor neurons. Neuropeptide Y enhances components of olfactory signal transduction pathway. NPY Y1 receptor plays an important role in mediating growth of olfactory receptor neurons.